How good are we at detecting deception? A review of current techniques and theories. (December 2019) - Nortje, Alicia; Tredoux, Colin
The task of discerning truth from untruth has long interested psychologists; however, methods for doing so accurately remain elusive. In this article, we provide an overview and evaluation of methods of detecting deception used in the laboratory and the field. We identify and discuss three broad approaches to detecting deception: measurement of non-verbal behaviour, verbal interview methods, and statement evaluation by humans and computers. Part of the problem in devising good methods for detecting deception is the absence of a sound understanding of deception in human lives. We thus consider three theories of deception – leakage, reality monitoring, and truth-default – and conclude that although promising, they do not yet provide an adequate foundation. We review 10 extant methods of detecting deception in the second part of the article, focusing at greatest length on the most widely used method in South Africa, the polygraph test of deception. Our conclusion is that non-verbal methods that work by inducing anxiety in interviewees are fundamentally flawed, and that we ought to move away from such methods. Alternate methods of detecting deception, including statement analysis, are considered, but ultimately our view is that there are currently no methods sufficiently accurate for practitioners to rely on. We suspect that a precondition for developing such measures is a coherent and validated theory.